The impact of relationship management of peace education on labour-management relations and workers welfare in selected industries in Nigeria (2007)
The study examines the impact of relationship management in peace education (independent variable) on labour-management relations and workers’ welfare (dependent variable) in industries. The study further examined the predictive effects of the independent variables on the dependent measure. The study is descriptive survey using 976 respondents randomly selected from eight industrial house unions. The main instrument used to collect data for the study was a set of questionnaire with 0.80 reliable coefficient. Multiple regression analysis was used as tool of analysis. The results indicated that taking the eleven variables that constitute relationship management to predict cordial labour-management relations in industries yielded a coefficient of multiple regression (R) of 0.879 and a multiple regression square ( R1) of 0.772. The result further indicated that all the individual independent variables would predict the dependent variable. In the light of these findings, it is suggested that the use of relationship management will promote a work environment where dialogue and values are explored and violence abhorred. It is further recommended that the introduction of relationship management in workers’ and management education will create a peaceful workplace culture and at the same time assist in reducing tension, strain, and stress thereby promoting workers’ welfare and productivity.